The Effect of Dual Competency-Based Human Resource Management on the Loyalty and Job Satisfaction of Academic Employees - Nurhidayah, Nurhidayah; Widodo, Widodo (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This research investigates the increasing significance of human resource management (HRM) in addressing the rise in competition within the education realm, especially in Islamic boarding school institutions. It is essential for academic personnel to not only exhibit strong academic skills but also to reflect Islamic principles. Consequently, the idea of dual competency, which merges professional academic abilities with religious morals, is viewed as a pertinent strategy. The goal of this study is to evaluate the application of HRM based on dual competency and how it relates to job satisfaction and loyalty among academic faculty at the Al-Multazam Islamic Boarding School Foundation located in Kuningan, West Java. This study adopts a qualitative methodology utilizing field research techniques. Data collection was carried out through interviews, observations, and reviewing documents, with informants chosen via purposive sampling, comprising permanent staff with at least one year of professional experience. Data analysis was performed through processes of reducing data, displaying findings, and drawing conclusions. The results demonstrate that implementing HRM grounded in dual competency, particularly through strategies for hiring and retaining staff, significantly contributes to enhancing job satisfaction and employee loyalty. The congruence between the skills of employees and the requirements of their roles, reinforced by a religiously inspired work environment, cultivates a stronger feeling of satisfaction and commitment to the organization. Importantly, this study highlights the development of spiritual loyalty, in which employees view their jobs as a type of worship (ibadah), thereby bolstering their internal motivation and ongoing commitment to the institution